What happened to the Early Precambrian granulite complexes of the Bug region (Ukrainian shield) and the Limpopo belt (South Africa) and how to stratify them? A tectonist’s view - О.Б. Гінтов (Геофизический журнал, 2022)
The author reviews two alternative approaches (stratigenic-metamorphogenic and deformation-metamorphogenic) to the geology and mapping of the Earth’s oldest crust rocks that were metamorphized in РТ-conditions of the granulite facies, on the examples of two granulite belts — the Bug area complex (Ukrainian shield) and Limpopo belt (Southern Africa).